2015
DOI: 10.1371/journal.pone.0144746
|View full text |Cite
|
Sign up to set email alerts
|

Durability and Effectiveness of Maraviroc-Containing Regimens in HIV-1-Infected Individuals with Virological Failure in Routine Clinical Practice

Abstract: IntroductionLimited data are available on the durability and effectiveness of maraviroc in routine clinical practice. We assessed the durability of maraviroc-containing regimens during a 30-month period, as well as their immunovirological and clinical efficacy, according to viral tropism in treatment-experienced individuals with viral load (VL) >50 copies/ml in the French Hospital Database on HIV.MethodsVirological success was defined as VL<50 copies/ml, immunological success as a confirmed increase of at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Maraviroc is the only CCR5 inhibitor used in the treatment of naive and treatment-experienced HIV patients. Maraviroc-containing regimen achieved high rates of viral suppression and immunological responses in individuals who had failed to respond to previous regimens ( 94 ) . Recent studies have shown that maraviroc can reactivate latent HIV in vivo ( 95 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Maraviroc is the only CCR5 inhibitor used in the treatment of naive and treatment-experienced HIV patients. Maraviroc-containing regimen achieved high rates of viral suppression and immunological responses in individuals who had failed to respond to previous regimens ( 94 ) . Recent studies have shown that maraviroc can reactivate latent HIV in vivo ( 95 ) .…”
Section: Discussionmentioning
confidence: 99%
“…8 Moreover, the tolerability profile of the drug makes MVC particularly appealing as a combination partner in antiretroviral therapy (ART). 9,10 Apart from the Motivate study, however, there are no large observational experiences describing the longterm efficacy and safety of salvage regimens with MVC for HIV-1 infection. Furthermore, experience with regimens containing MVC and newer antiretroviral agents is limited.…”
Section: Introductionmentioning
confidence: 99%
“…8 Moreover, the tolerability profile of the drug makes MVC particularly appealing as a combination partner in antiretroviral therapy (ART). 9,10…”
Section: Introductionmentioning
confidence: 99%